Towards a Unified Vertical Datum in Arab Region - Saad, Abdallah A.; Elsayed, Mona S.; Abdelfatah, Shimaa F. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
In Arab region, there are several Local Vertical Datums (LVD). Most of these datumsare based on averaging sea level measurements of a single Tide Gauge (TG) or frommultiple TGs.One of the main reasons which negatively affecting the huge regional projects betweenArab countries as transportation lines, Petroleum Pipelines, electricity, and otherprojects which require heights, is the difference in SST at tide gauge sites anddifferences in measuring techniques. Therefore the Precise geoid determination isconsidered an important step in eliminating these differences as it represents the basefor determination the regional geoid model. This study focuses on presenting twoproposals for unification the vertical datum in Arab region and the proposedimplementation strategy. Review of available data from previous studies. Provide thebest techniques to update, tie, and unify the data in all Arab countries, commensuratewith the modern technological development.